A Change in Work-Family/Life or a Return to Traditional Normative Patterns in Spain? Systematic Review - Morero-Mínguez, Almudena; Ortega-Gaspar, Marta (Frontiers in Sociology, 2022)
Family policies to reduce conflict in work-life balance and promote gender equality advanced significantly at the legislative level in Spain in the first decades of the 21st century. These advances include the 2007 Law for Equality between Men and Women and the extension of paternity leave to 16 weeks in 2020. However, advances in care work and at the professional level have been limited. The COVID-19 pandemic has intensified existing imbalances in family-work responsibilities in general and the ICT gender gap in particular. In crisis situations, women adopt the role of caregivers more easily than men, and women with fewer educational, economic, and job resources are more likely to assume this role, contributing to increasing gender inequalities at work and in the family. COVID-19 has exposed these imbalances, highlighting the need for new narratives and laws that encourage gender equality. Post-COVID-19 scenarios thus present an opportunity for reflection and progress on Spanish family policy. From this perspective, the paradigm of work-family conflict, although interesting, must be examined and resignified. This article proposes to critically resignify the paradigm of work-family conflict based on the new narrative generated by Covid-19. The present analysis suggests a resignification that should involve changing the expectations and practices around work-family balance, based on family diversity, job insecurity, the technological revolution, and new masculinities. It is proposed a prior reflection to clarify definition of the indicators and indexes that enable operationalization of the concept of work-family reconciliation. It is expected that these measures will help to facilitate practical application of reconciliation in areas such as public or/and private organizations, while also enabling international comparative analysis.